The Japanese species of Monoctenus (Hymenoptera: Diprionidae) - Hara, Hideho; Nagase, Hirohiko (Zootaxa, 2023)
The Japanese species of Monoctenus are revised and keyed. The following seven species and subspecies are recognized: M. cryptomeriae Togashi, 2001 from Honshu, M. decoratus Takeuchi, 1940 from Honshu, M. fujisanus Togashi, 2001 from Honshu, M. itoi Okutani, 1958 from Honshu, M. kondoi Hara, sp. nov. from Honshu, M. nipponicus Takeuchi, 1940 from Honshu and Awaji Island and M. obscuratus hokkaidonis Hara, subsp. nov. from Hokkaido. Their descriptions or additional descriptions are given. The host plant of M. kondoi is Juniperus rigida Siebold et Zucc. The host plant of M. obscuratus hokkaidonis is Juniperus communis L. var. montana Aiton.